Critical pre- and postoperative factors in evaluating ptosis - Cornwell, Jordan N.; Smith, Claire S.; Lucarelli, Katherine M.; Sones, Alexander; Rootman, Daniel B. (Frontiers in Ophthalmology, 2025)
BackgroundBlepharoptosis repair is a common eyelid surgery worldwide, however technique and outcome measurements vary widely.ObjectiveThis study aims to determine a consensus on pre- and postoperative factors important to oculoplastic surgeons in the evaluation of ptosis.MethodsOculoplastic surgeons were queried to describe 10 or more variables important for pre- and postoperative evaluation of ptosis and subsequently rate them on a 5-point Likert scale. A nominal group meeting determined a consensus on the 10 most important pre- and postoperative factors based on the previous survey responses. Mean and standard deviation for Likert score responses were compared using a student’s t-test.ResultsOne hundred and sixty-three respondents contributed a total of 1,909 open-ended responses. The two most cited factors were levator function (91.4%) and upper marginal reflex distance (87.7%). Known secondary causes of ptosis (75.5%), health of cornea and tear film (58.9%) and brow elevation/compensation (55.2%) were reported as important by over 50% of the respondents. The final variables were categorized into four groups: Causes of Ptosis, Surgical Planning, Anatomy and Symmetry, and Ptosis-Related Quality of Life.ConclusionA cohort of ASOPRS oculoplastic surgeons reached a consensus on a critical set of variables important for ptosis evaluation.